The COVID-19 experience in the Fiji Islands: some lessons for crisis management for small island developing states of the Pacific region and beyond. Issue 1 (2nd January 2022) - Singh, Rup; Lal, Sumeet; Khan, Mohsin; Patel, Arvind; Chand, Ronal; Jain, Devendra Kumar
Abstract : The COVID19 global pandemic has seriously disturbed Fiji, its people and the economy. Consequently, crisis management has been highly challenging in this small and vulnerable economy. Although the number of positive cases was low, the economic impact of COVID19 has been significant. In this paper, we identify several crisis management issues to better deal with the pandemic. These discussions can potentially improve Fiji's response strategies and initiatives to safeguard public health and economic activity. Our evaluation indicates room for learning and innovation in Fiji's health care services to ensure resilience and effective response mechanisms. The suggestions are not only useful for Fiji but also for other similar economies in the region. These suggestive strategies can work as proactive measures to combat second wave impact yet to come.